ARTP mutagenesis of phospholipase D-producing strain Streptomyces hiroshimensis SK43.001, and its enzymatic properties. Issue 12 (December 2022) - Li, Chenchen; Xia, Yu; Li, Mengli; Zhang, Tao
Abstract: Phospholipase D (PLD) is a group of enzymes that act on phospholipid molecules, which is widely used in the fields of food and medicine. PLD is extracted from animals and plants with low transesterification activity and high price. Therefore, it is benefit to screen an efficient PLD producing strain from microorganisms. A highly productive strain of PLD with transphosphatidylation activity, named Streptomyces hiroshimensis SK43.001, was screened from soil in our laboratory and mutated using atmospheric room temperature plasma (ARTP). A mutant strain SK43.001-11 with the highest enzyme activity and superior genetic stability was obtained, and its fermentation enzyme activity was 5.3 U/mL, which was 82% increased comparing to wild strain. The purification of PLD showed that the specific enzyme activity increased to 49.48 U/mg, which was 54.37-fold higher than that of the crude enzyme, with a recovery of 32.31%. In addition, enzymatic properties of PLD have revealed that the optimal pH and temperature were 7.0 and 60 °C, respectively. Metal ion Mg 2+ and surfactant Triton X-100 made the enzymatic activity increased by 16% and 100%, respectively. The reaction kinetic parameters showed that the mutant PLD had higher affinity for the substrate of egg PC and better catalytic efficiency with K m, V max and K cat of 30.20 mmol/L, 99.70 μmol/min and 76.33 s −1, respectively. This study may provide important inspiration for obtaining high enzyme activity strains with PLD. Abstract : Phospholipase D; ARTP; Purification; Enzymatic properties; Streptomyces hiroshimensis .